THE GINI COEFFICIENT. DECOMPOSITION AND OVERLAPPING - ARIZE, Augustine C.; BAKAREZOS, Paraskevas; KASIBHATLA, Krishna M.; MALINDRETOS, John; PANAYIDES, Alex (Journal of Advanced Studies in Finance, 2014)
The purpose of this paper is to present the process of decomposition and its relation to the Gini coefficient with emphasis on the explanation of the nature of the overlapping component (or interaction effect) which arises during decomposition and it is usually treated as an awkward by-product of this process. It is shown that exact decomposition without the presence of the overlapping effect is possible even when group income distributions are overlapping under condition that data on individual incomes are available. The problem is purely mathematical and it arises when decomposition is accompanied by replacement individual income comparisons with differences in mean group income between pairs of groups. In this case, the overlapping component can be completely separated from the other two, the “within” and “between” inequality components. Furthermore, the case of grouped data is considered that does not allow exact separation of the component.